Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year Three, 2013 – Agriculture, Climate and Employment - Tvedten, Inge; Rosário, Carmeliza; Tuominen, Minna; Samuel Jones (ORGUT Consulting AB, 2013)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; institutions / instituições; poverty / pobreza

Brazil’s cooperation in African agricultural development and food security - Patriota, Thomas Cooper; Pierri, Francesca Maria (Agricultural development and food security in Africa: The impact of Chinese, Indian and Brazilian investments, 2013)
Brazil’s agricultural cooperation in Africa is shifting from small localised projects to more structured ventures capable of having larger and more durable impacts on African rural development. Nonetheless, it still suffers from in adequate coordination between relevant ministries and other governmental bodies. However, the coexistence of two agricultural development paradigms in Brazil’s cooperation should not be seen as incoherent. Rather, it is a direct reflection of the twotiered structure of Brazil’s agricultural policy framework, with support for agribusiness provided by the Ministry of Agriculture, Livestock and Food Supply (Ministério da Agricultura, Pecuária e Abastecimento) and for family farming by MDA. Consequently, the Brazilian government has attempted to present both as part of the Brazil–Africa Dialogue to enable African ministers to learn about the wide range of policies implemented in Brazil. Combined with demanddriven horizontal cooperation, the approach has enabled African countries to choose between (and sometimes combine) approaches to promoting their agriculture.
Keywords: G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; rural development / desenvolvimento rural; south-south cooperation / cooperação sul-sul

Brazil, biofuels, and food security in Mozambique - Thali, Kai (Agricultural development and food security in Africa: The impact of Chinese, Indian and Brazilian investments, 2013)
This chapter, therefore, explores the role of agriculture in Brazilian develop ment assistance programmes and direct investment in Africa, focusing on the potential tensions between biofuel feedstock and food production. After a brief overview of the history of Brazil’s own agricultural development and the country’s relations with Africa, the chapter delves into an examination of Brazilian engagement in the conjoined agricultural and energy sectors of Mozambique, a country that possesses large tracts of arable land and is considered a prime site for biofuel production. The chapter critiques Brazil’s development assistance and investment model and presents ways to improve its effectiveness in order to generate greater benefits for the Mozambican people.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; agriculture / agricultura